PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, DAN LINGKUNGAN KERJA NON FISIK TERHADAP PERILAKU INOVATIF - RIO NARDO; SUSI EVANITA; SYAHRIZAL SYAHRIZAL (Universitas Islam Negeri Imam Bonjol Padang, 2018)
This study aims to examine the significance of the influence of transformational leadership, and non-physical work environment, on innovative behavior with work motivation as a mediator for employees of tour and travel companies in West Sumatra. This study uses a quantitative approach with a total sample of 110 respondents selected using the proportional random sampling technique. The results of the study prove that: (1) Transformational leadership has no significant effect on innovative behavior; (2) Non-physical work environment has a significant effect on Innovative Behavior; (3) Work motivation becomes a mediator on the effect of transformational leadership on innovative behavior; (4) Work motivation becomes the mediator of the influence of the non-physical work environment on the innovative behavior of employees.